Please help me to Solve these Diff. Equ.s by transforming an independent variable:

(1) $\displaystyle \frac{d^2y}{dx^2}+\frac{2}{x}\frac{dy}{dx}-n^2y=0$

(2) $\displaystyle \frac{d^2y}{dx^2}+\frac{2}{x}\frac{dy}{dx}+n^2y=0$

(3) $\displaystyle (x-3)\frac{d^2y}{dx^2}-(4x-9)\frac{dy}{dx}+3(x-2)y=0$

(4) $\displaystyle (1-x^2)\frac{d^2y}{dx^2}+3x\frac{dy}{dx}+y=0$

(5) $\displaystyle \frac{d^2y}{dx^2}+4x\frac{dy}{dx}+4x^2y=0$

(6) $\displaystyle x\frac{d^2y}{dx^2}-(2x-1)\frac{dy}{dx}+(x-1)y=0$

(7) $\displaystyle \frac{d^2y}{dx^2}+x\frac{dy}{dx}-y=f(x)$

(8) $\displaystyle (x\sin x+\cos x)\frac{d^2y}{dx^2}-x\cos x\frac{dy}{dx}+ y\cos x$

Please help me, 2moro I have to explain it..